Analyses of cloud characteristic during Malaysian 2014 flood event - Basri, Atikah Balqis; Ismail, Ahmad Fadzil; Khairolanuar, Muhamad Haziq; Mohd Sobli, Nuurul Hudaa; Badron, Khairayu; Hasan, Mohammad Kamrul (Indian Society for Education and Environment, 2016)
Floods refers to the condition of great overflow of water over a dry land. In malaysia, monsoon flood which cause by the heavy rain in monsoon seasons regularly hits the country. A criteria of the cloud based on horizontal and vertical profile of radar reflectivity have been analyzed in this paper to estimate flood event. The values of the thickness and the size of the cloud are estimated from the analysis. In this paper, we analyze the river basin data and radar data in the duration of flooding time, T for the specific area covered by meteorological radar and rain gauge data. The procedure was applied to 14 days precipitation phenomenon observed in Kota Bharu, Kelantan (Malaysia) from 13 December 2014 until 26 December 2014. The objective of this paper is to analyse the distinctiveness of the cloud during flood events. The result shows that during the critical time of flood disaster, the cloud shows largest size of 13070.6 km2 and the thickness appeared to be the largest at almost 10.2 km during the beginning of the rain fall. The analysis helps us to understand the cloud characteristics hence in future flood estimation model can be constructed and modelled.